Bahasa Indonesia Bahasa Indonesia: Bahasa Indonesia - Pratiwi, Rika Luthfia; Widjayatri , RR. Deni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
The purpose of this study was to determine the effect of sorting color puzzle games on the problem-solving ability of 5-year-olds. Problem-solving skills are part of one aspect of child development, especially the cognitive aspect. Problem-solving ability is the ability of individuals to use their thought process to solve a problem by gathering facts, analyzing the information obtained, and preparing alternative problem solving. This research uses qualitative research methods with a deductive approach. Qualitative research is research conducted by collecting data systematically, arranging data according to certain categories, interpreting and describing data obtained through interviews, observations, and interviews, observation and documentation. In this study, researchers conducted observations and interviews with children. Observations were made on 4 children aged 5 years in Balaraja District, Tangerang Regency, Banten. The results of this study showed that color puzzle games had an impact on the problem-solving ability of 5-year-olds. This is evidenced by the results of the data obtained by the researchers from observation activities, namely in the first test of the color puzzle sorting game, there were 2 children who received an assessment Start playing development and 2 children develop as expected. Then, the results obtained in the second experiment showed an improvement in each child. 3 children are considered to develop very well and 1 child develops as expected.